2015
DOI: 10.1021/acsami.5b02171
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Anchored MnO Nanosheets as an Anode for High-Rate and Long-Life Lithium-Ion Batteries

Abstract: Developing electrode materials with high rate as well as prolonged cycle is particularly necessary for the ever-growing market penetration of electric vehicles and hybrid electric vehicle. Herein, we demonstrate a facile and efficient strategy to synthesize MnO/C hybrid via freeze-drying followed by thermal treatment in N2 atmosphere. The MnO nanosheets are firmly anchored onto carbon layers to form MnO/C hybrid. When used as an anode in lithium-ion batteries, the typical MnO/C hybrid displays a high initial C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 65 publications
9
72
0
Order By: Relevance
“…As reported in references, the first discharge plateaus of MnO and Fe 2 O 3 were generally located at around 0.26 V (reduction of Mn 2 + to Mn) [14] and 0.68 V (reduction of Fe 3 + to Fe). Therefore, the broad reduction peaks at 0.32 V in CV profile of MnO@MnFe 2 O 4 @rGO at ambient temperature could be considered as the consequence of overlap of these peaks ( Figure S9a).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…As reported in references, the first discharge plateaus of MnO and Fe 2 O 3 were generally located at around 0.26 V (reduction of Mn 2 + to Mn) [14] and 0.68 V (reduction of Fe 3 + to Fe). Therefore, the broad reduction peaks at 0.32 V in CV profile of MnO@MnFe 2 O 4 @rGO at ambient temperature could be considered as the consequence of overlap of these peaks ( Figure S9a).…”
Section: Resultssupporting
confidence: 71%
“…(1) the synthesis strategy may be proved to be cost‐effective and scalable, and artificially designed nanoparticles were allowed to avoid adverse size‐effects and potentially shape‐dependent kinetic and thermodynamic constraints for conversion reaction; (2) artificially designed core/shell structure provided an unique opportunity to integrate MnO and MnFe 2 O 4 into one whole particle with an ordered and controllable microstructure and particle size. In addition, core/shell structured nanocomposites may sprout additional lithium storage sites, leading to an outstanding performance such as enhanced reversible capacity;, and (3) enhanced kinetics at 60 °C has given rise to an excellent reversible capacity of 1067 mAh g −1 at a current density of 500 mA g −1 after 300 cycles…”
Section: Resultsmentioning
confidence: 99%
“…The main peak at 284.8 eV belongs to the sp 2hybridized graphite carbon. [15] Two weak peaks at 286.2 and 288.3 eV belong to CO and CO, respectively. [16] The N 1s core-level spectrum can be well fitted into a pyrodinic nitrogen (N-6) at 398.4 eV and a pyrrolic nitrogen (N-5) at 400.4 eV.…”
Section: Structure and Morphologymentioning
confidence: 99%
“…The MnO/Co structure exhibited improved reversible chargedischarge stability and it was concluded that deposition of the Co nanocrystals and the formation of a CoO surface layer were responsible for the enhanced performance. In addition, a significant number of previous reports on MnO-based materials show a dramatic increase in the capacity retention during cycling [13][14][15][16][17][18][19][20][21][22][23] which is most likely due to the formation of phases with higher oxidation states and correspondingly higher theoretical capacities (such as Mn 3 O 4 (936 mAhg −1 ), Mn 2 O 3 (1019 mAhg −1 ) [11], MnO 2 (1230 mAhg −1 ) [3]). However, in most cases even these materials exhibit poor high rate charge-discharge performance.…”
Section: Introductionmentioning
confidence: 99%